Echocardiographic assessment of right ventricle adaptation to endurance training in young rowers – speckle tracking echocardiography - Konopka, M; Krol, W; Burkhard-Jagodzinska, K; Jakubiak, A; Klusiewicz, A; Chwalbinska, J; Pokrywka, A; Sitkowski, D; Dluzniewski, M; Braksator, W (Biology of Sport, 2016)
The aim of this study was to determine the relationship between the degree of cardiorespiratory fitness and the function of the right ventricle (RV). 117 rowers, age 17.5±1.5 years. All subjects underwent cardiopulmonary exercise. Standard echocardiography and 2D speckle tracking echocardiography with evaluation of longitudinal strain in each segment of the RV (basal – RVLS-B; mid – RVLS-M, apical – RVLS-A) and global RV free-wall strain (RVLS-G) were performed. RVLS-B values were lower compared to the RVLS-M (-25.8±4.4 vs -29.3±3.5; p<0.001) and RVLS-A values (-25.8±4.4 vs -26.2±3.4; p=0.85). Correlations between VO2max and RVLS were observed in men: RVLS-G strain (r = 0.43; p <0.001); RVLS-B (r = 0.30; p = 0.02); RVLS-M (r = 0.38; p = 0.02). A similar relationship was not observed in the group of women. The strongest predictors corresponding to a change in global and basal strain were VO2max and training time: RVLS-G (VO2max: β = 0.18, p = 0.003; training time: β = -0.39; p = 0.02) and RVLS-B (VO2max: β = 0.23; p = 0.0001 training time: β = -1.16; p = 0.0001). The global and regional reduction of RV systolic function positively correlates with the level of fitness, and this relationship is observed already in young athletes. The character of the relationship between RV deformation parameters and the variables that determine the physical performance depend on gender. The dependencies apply to the proximal fragment of the RV inflow tract, which may be a response to the type of flow during exercise in endurance athletes.